Persepsi Masyarakat Minang terhadap Tradisi Badoncek dalam Pernikahan Orang Minangkabau di Kota Medan - Astika, Julia; Monang, Sori; Syam, Abdi Mubarak (YASIN, 2024)
This research is entitled “Minang People’s Perception of the Badoncek Tradition in Minangkabau Weddings in Medan City”. The focus of this research is how the history, benefits and perception of the Minang people toward the Badoncek Tradition in Binjai Village, Medan Denai District, Medan City. The purpose of this study is as additional reference material for future research. This research uses qualitative methods and conducts research directly using reference sources from indigenous figures there. From the results of research that has been conducted in the field that the perception of the Minang people towards the Badoncek tradition is very accepted by the surrounding community, especially the Minang Pariaman community who brought the tradition to overseas and continues to be preserved and developed in Binjai Village, Medan Denai District, Medan City.